Trends in Geomatics An Earth Science Perspective - Abdalla, Rifaat (IntechOpen, 2019)
The applications of geomatics technology in its broader context have resulted in significant progress in the field of earth science. This book provides brief coverage on some trends in geomatics technology as it relates to earth scientists. The development in geomatics, whether GIS, remote sensing, GPS or photogrammetry, can be seen from trends in the applications of Big Data, Smart City, Internet of Things (IoT), the use of augmented reality and utilization of unmanned aerial vehicles (UAVs) and in the impact of machine learning and AI on geomatics.